Real-Time Carpooling Application for Android Platform (International Journal of Engineering and Computer Science, 2017)
— in today’s world, everyone commuting from one place to another for specific reasons. E.g. school, job, excursion etc. Carpooling is the application based on android platform help sharing of car journeys so that more than one person travels in a same car. By adopting this application, users, will help to reduce high amount of CO2 emission because of car. Carpooling reduces each person’s travels costs such as fuel costs, parking space, tolls, and the stress of driving. Carpooling application is a more environmentally friendly and sustainable way to travel as sharing journeys. Carpooling is more suitable, especially during high fuel prices and high pollution periods. Carpooling is Android based application that provide more security and easy way to find a car for journey. Also it is working on mobile device which makes it more usable and makes the service more dynamic